Heutagogical approach to music learning in vocational schools - Y. Sukmayadi; F. Sella; H. I. Midyanti (Russian State Vocational Pedagogical University, 2022)
Introduction. Music is one of the areas of expertise and skills existing in vocational schools in Indonesia, where students must master music in theory and practice. Due to the COVID-19 pandemic, music teachers are encouraged to design alternative learning methods in order to facilitate the students to learn music. This challenges the music teachers to provide interesting and well-delivered material during online learning since the teachers of vocational education have to adapt quickly and prepare the students to be ready in facing the today's challenges. In addition, the use of information and communication technology in teaching and performing music is growing rapidly, thus, the music teachers must master computer technology to address the complexities of today's music industry, and support the music learning process in theory and practice. The heutagogical approach is believed to be an innovative and trending approach to be applied in the music learning process, since it can adapt to the current changing times. It can also assist teachers to guide music theory and practice, develop and deliver direction and discussion through technology assistance with learning materials agreed in the classroom.The aim of this article is to analyse the application of a heutagogical approach that focuses on improving learning, overall learning opportunities, and developing independent skills with technology assistance on music subjects in vocational schools in Bandung (West Java, Indonesia).Methodology and research methods. This research employs grounded theory method by providing explicit analytical strategies with the ultimate goal of obtaining theories about certain processes, actions, or interactions that come from the teacher's point of view in teaching music in vocational schools.Results and scientific novelty. It was found that teaching processes with heutagogical approach tend to be student-centred, enabling students to learn independently through self-determination, since it is the real implementation of student-centred educational theory that can help students hone skills and metacognition and reflect their own learning experience faster.Practical significance. The current research aims at helping students studying music in vocational schools to apply self-determined learning, hence they can determine what to learn, how to learn it, when to learn, and where to get information to achieve the learning objectives.Thus, students can decide when the best time to study music, explore their musical knowledge, and practice their music skills. In addition, students can be trained to design music lessons, build space patterns and learning opportunities, and develop themselves individually; hence that they can be responsible for the learning objectives they designed for themselves. As for the teachers, they can play their role as a guide and facilitator who can direct students in achieving their learning objectives.